FMUiL: An open-source package for in-the-loop simulations with functional mock-up units - Klemets, K.; Bouzoulas, D.; Manngård, M.; Böling, J.M. (Elsevier BV, 2026)
Functional Mock-up Units in the Loop (FMUiL) is an open-source Python package designed to support virtual commissioning and design phases of projects. It combines the FMI and OPC UA standards to enable the cosimulation between simulation models, software, and hardware. Since the FMI standard does not specify how co-simulation between FMUs and external systems should be handled, FMUiL uses the OPC UA communication protocol, which is widely adopted in the process automation industry, to manage the data exchange between devices and systems. Simulation models are wrapped as OPC UA servers that can be connected to external servers. To simplify experiment setup and ensure reproducibility, FMUiL uses YAML configuration files to define simulation scenarios and experiments, which can then be executed through the provided command-line interface. This paper documents the architecture and functionality of the FMUiL package, describes how experiments are configured, and demonstrates its use through practical examples.